2013
DOI: 10.1111/bcpt.12121
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcaemia after an Occult Calcium Channel Blocker Overdose: A Case Report and Literature Review

Abstract: Hypocalcaemia is a rare complication of calcium channel blocker overdose, having been reported only once previously (J Toxicol Clin Toxicol, 1992, 30, 309). In this article, we report a case of a 37-year-old woman who developed hypocalcaemia after a verapamil overdose, review the literature and propose a mechanism for this rare finding.Calcium channel blockers (CCBs) are responsible for a large number of drug-related fatalities. The 2011 Annual report of the American Association of Poison Control Centers' Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In Cohort 2 the PrecisionLife platform identified 18 disease signatures in 80 hospitalized patients with serum calcium values lower than 9.26 mg/dl ( Supplementary Figure 7 ). Out of these, only four signatures were co-associated with the use of the dihydropyridines (calcium channel blockers) and proton-pump inhibitors which may have an effect on calcium homeostasis 28,29 . The hypocalcemia disease signatures were associated with COVID-19 symptoms such as pneumonia and respiratory failure, and comorbidities including diabetes, hypertension and anemia.…”
Section: Resultsmentioning
confidence: 99%
“…In Cohort 2 the PrecisionLife platform identified 18 disease signatures in 80 hospitalized patients with serum calcium values lower than 9.26 mg/dl ( Supplementary Figure 7 ). Out of these, only four signatures were co-associated with the use of the dihydropyridines (calcium channel blockers) and proton-pump inhibitors which may have an effect on calcium homeostasis 28,29 . The hypocalcemia disease signatures were associated with COVID-19 symptoms such as pneumonia and respiratory failure, and comorbidities including diabetes, hypertension and anemia.…”
Section: Resultsmentioning
confidence: 99%
“…In Cohort 2 the PrecisionLife platform identified 18 disease signatures in 80 hospitalized patients with serum calcium values lower than 9.26 mg/dl ( Supplementary Figure 7 ). Out of these, only four signatures were co-associated with the use of the dihydropyridines (calcium channel blockers) and proton-pump inhibitors which may have an effect on calcium homeostasis ( 27 , 28 ). The hypocalcemia disease signatures were associated with COVID-19 symptoms such as pneumonia and respiratory failure, and comorbidities including diabetes, hypertension, and anemia.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 A single-center retrospective reported that 19% of the patients receiving the drug developed acute kidney injury (AKI). 5 However, the cause of AKI was not clarified in the study results. Wanchoo et al 6 reported a case of acute interstitial nephritis (AIN) secondary to the drug in 2016.…”
Section: Muge Gulenmentioning
confidence: 87%
“…To the Editor: Overdose of antihypertensive drugs may cause hypotension, shock, dysrhythmias, electrolyte disturbances, metabolic disorders, seizures, agranulocytosis, hepatic damage, renal damage, noncardiogenic pulmonary edema, angioneurotic edema, and death. [1][2][3][4][5][6] According to the data from the American Association of Poison Control Centers' 2017 annual report, a total of 108,614 cases of poisoning were reported with cardiovascular drugs. b-Blockers and calcium channel blockers are accused of more than half of mortality due to antihypertensive agents.…”
Section: Severe Polyantihypertensive Drug Poisoning: Unresponsive To ...mentioning
confidence: 99%
See 1 more Smart Citation